2018
DOI: 10.30843/nzpp.2018.71.145
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the biocontrol beetle, Cassida rubiginosa, on the secondary weed target, marsh thistle (Cirsium palustre)

Abstract: The folivorous beetle Cassida rubiginosa was introduced to New Zealand to control the weed, Californian thistle (Cirsium arvense). Although Californian thistle is the primary host, many other thistles are accepted hosts. The objective of this study was to test if the beetle can reduce the fitness of marsh thistle (Cirsium palustre). A potted plant experiment was established with four treatments (0, 50, 100, and 200 larvae/plant). Plant growth (width, height, and number of branches) and reproductive performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Overall, feeding damage from larvae of Cassida rubiginosa did not affect the growth (height, or biomass) or reproductive performance (number of seedheads and seeds) of Carduus pycnocephalus.This result was expected based on a previous study where the same larval densities were applied to Cirsium palustre and had no significant impact on the weed (Hettiarachchi et al 2018). However, we expected that the effect of the beetle would be expressed under the constrained growth conditions imposed by small pot size.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Overall, feeding damage from larvae of Cassida rubiginosa did not affect the growth (height, or biomass) or reproductive performance (number of seedheads and seeds) of Carduus pycnocephalus.This result was expected based on a previous study where the same larval densities were applied to Cirsium palustre and had no significant impact on the weed (Hettiarachchi et al 2018). However, we expected that the effect of the beetle would be expressed under the constrained growth conditions imposed by small pot size.…”
Section: Discussionsupporting
confidence: 72%
“…The maximum feeding damage reached was approximately 50% defoliation in the highest larval density treatment. This level of feeding damage is lower than the 60 to 70% defoliation reported for the same larval density (200 per plant) in the experiment with Cirsium palustre (Hettiarachchi et al 2018) and, therefore, was understandable that it did not have an impact. A similar experiment using Carduus nutans (nodding thistle) reported that 23% defoliation by larvae of Cassida rubiginosa had no effect on plant growth or seed production (Cartwright & Kok 1990).…”
Section: Parametermentioning
confidence: 54%
See 2 more Smart Citations
“…rubiginosa was also released in New Zealand for the same purpose 33 . In both new locations, the beetle alone only slightly reduced thistle performance, although its effect may be stronger in conjunction with other natural enemies and competitors 34,35 . Throughout its distribution range, C .…”
Section: Study Speciesmentioning
confidence: 83%